Study of Pertamax and Pertamax Turbo Comparison on the Performance of 135CC 2-Stroke Motorcycles - Sefnath J Etwan Sarwuna; Willem Marthinus Eric Wattimena; Ekinov Limbong (Magister Teknik Mesin Universitas Pancasila, 2026)
Advances in vehicle technology and issues related to fossil fuel reserves have prompted Pertamina, as a fuel producer, to produce environmentally friendly, economical, and fuel-efficient fuels that also maximize engine performance. There are several types of motor fuels, including premium, pertalite, pertamax, and pertamax turbo. Each type has different specifications and octane number. The higher the octane number of the fuel used in a vehicle, the better the engine performance, while also reducing carbon deposits in the combustion chamber and producing emissions that are not harmful to the environment. Therefore, this study examines the effect of using Pertamax and Pertamax Turbo fuels on the torque and power of a 135cc RX-King motorcycle. This research is experimental in nature, using a Power Dyno testing device. The motorcycle is placed on the Power Dyno chassis and connected to a computer device, after which the torque and power values at certain revolutions are displayed on the monitor screen. The results of the study show that Pertamax fuel produces a maximum torque value of 9.00 Nm at 7116 RPM and power of 9.17 HP at 8181 RPM, while Pertamax Turbo fuel produces a maximum torque value of 9.26 Nm at 7250 RPM and power of 10.71 HP at 8181 RPM. This shows an increase in the performance of the Yamaha RX-King 135 engine when using Pertamax Turbo, which has a higher octane number than Pertamax.